Heterozygous desmin gene (DES) mutation contributes to familial dilated cardiomyopathy. Issue 4 (April 2021) - Huang, Ying-shuo; Xing, Yun-li; Li, Hong-wei
Familial dilated cardiomyopathy (FDCM) is characterized by high genetic heterogeneity and an increased risk of heart failure or sudden cardiac death in adults. We report the case of a 62-year-old man with a 2-month history of shortness of breath during activity, without paroxysmal nocturnal dyspnea. The patient underwent a series of examinations including transthoracic echocardiography, coronary arteriography, transesophageal echocardiography, and myocardial perfusion imaging. After excluding secondary cardiac enlargement, he was diagnosed with dilated cardiomyopathy (DCM). His sister had also been diagnosed with DCM several years before. Genetic sequencing analysis revealed that the patient, his sister, and his son all had the same mutation in the desmin gene ( DES ) (chr2-220785662, c.1010C>T). Genetic testing confirmed a heterozygous DES mutation contributing to FDCM. In this case, the etiology of the patient's whole-heart enlargement was determined as FDCM with DES gene mutation. This is the first report to describe DES c.1010C>T as a cause of FDCM.